1995
DOI: 10.1093/oxfordjournals.humrep.a136285
|View full text |Cite
|
Sign up to set email alerts
|

Immunology: Outcome of pregnancy in women with recurrent spontaneous abortion following immunotherapy with allogeneic lymphocytes

Abstract: The efficacy of immunotherapy in the prevention of habitual abortion remains controversial. It has been suggested that the benefits are predominantly due to psychological factors. We have evaluated the success of pregnancy outcome following immunotherapy with allogeneic lymphocytes, in relation to the subsequent development of anti-paternal cytotoxic antibodies (APCA). It was observed that in women who developed an APCA titre of > or = 1:16, live births occurred in 16 out of 21 cases (76%), while only two out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
(33 reference statements)
1
10
0
2
Order By: Relevance
“…In some other clinical investigations, it was shown that the efficacy of immunotherapy is related to the immune response by allogeneic lymphocytes and is not simply a placebo effect. Those studies suggest that allogenic lymphocytes may play an important role in maintenance of pregnancy (18,19); consistent with this, our results also suggest high clinical efficacy of alloimmunization. We know that paternal lymphocytes have a better human lymphocyte antigen (HLA) paternal blockage.…”
Section: Discussionsupporting
confidence: 91%
“…In some other clinical investigations, it was shown that the efficacy of immunotherapy is related to the immune response by allogeneic lymphocytes and is not simply a placebo effect. Those studies suggest that allogenic lymphocytes may play an important role in maintenance of pregnancy (18,19); consistent with this, our results also suggest high clinical efficacy of alloimmunization. We know that paternal lymphocytes have a better human lymphocyte antigen (HLA) paternal blockage.…”
Section: Discussionsupporting
confidence: 91%
“…Some of the recent studies demonstrated that PL immunotherapy significantly reduced the overactivity of NK cells and Th-1 pattern of cytokines in women with RSA [46][47][48]. However, our earlier studies have shown that the efficacy of lymphocyte immunotherapy was related to immune response to allogenic lymphocytes [17,24]. We further demonstrated that MLR-Bf developed during pregnancy and alloimmunotherapy was IgG 3 in nature [26].…”
Section: Introductionmentioning
confidence: 68%
“…Alloimmunity has been indicated in several studies by showing an association of habitual abortion with an increased sharing of human leukocyte antigens (HLA) with the father that may prohibit the production of antipaternal cytotoxic antibodies (APCA), anti-idiotypic antibodies (Ab2) and mixed lymphocyte reaction blocking antibodies (MLR-Bf) in the mother. Paternal lymphocyte (PL) immunization is an effective treatment for unexplained recurrent spontaneous abortions, as it was attributed to the production of APCA [17,22,[32][33][34], Ab2 [21,35,36] and MLR-Bf [2,17,20,26,27,31,32,37 -45] during pregnancy in women with RSA. Some of the recent studies demonstrated that PL immunotherapy significantly reduced the overactivity of NK cells and Th-1 pattern of cytokines in women with RSA [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Ранние исследования показали, что дефицит указанных антител у женщин с наличием в анам-незе ПНБ или беременных с угрозой выкидыша [2,4] ассоциируется с высоким сходством партне-ров по HLA-антигенам гистосовместимости [7,17,34]. Соответственно, для профилактики и ле-чения ПНБ был предложен метод иммунизации лимфоцитами отца, позволяющий индуцировать появление БФ [2,4] , Филиппинах 12 и др., однако однозначного мнения в отношении эф-фективности данного метода так и не сложилось.…”
Section: Introductionunclassified
“…Соответственно, для профилактики и ле-чения ПНБ был предложен метод иммунизации лимфоцитами отца, позволяющий индуцировать появление БФ [2,4] , Филиппинах 12 и др., однако однозначного мнения в отношении эф-фективности данного метода так и не сложилось.…”
Section: Introductionunclassified